电致变色器件控制电路 (2023)
本发明公开了一种电致变色器件控制电路，包括：充电电路，用于在电压输入端有电源电压输入时仅存储工作电压，并在所述电压输入端无所述电源电压输入时才释放所述工作电压；检测电路，用于检测外部环境数据并产生环境数据信号；控制电路，用于接收所述工作电压和所述环境数据信号并产生控制信号；输出电路，用于根据所述控制信号对所述电致变色器件进行充放电。本发明提供的一种电致变色器件控制电路解决了现有技术中电路断电情况下无法维持电致变色器件长时间高反射率的问题，实现了对电致变色器件的反射率多方面控制和维持稳定的效果。 The invention relates to the technical field of electrochromism, and particularly discloses an electrochromism device control circuit which comprises a detection circuit used for detecting external environment data and generating environment data signals; the control circuit is used for receiving the working voltage and the environment data signal and generating a control signal; and the output circuit comprises a constant-voltage output circuit, and the constant-voltage output circuit is used for charging and discharging the electrochromic device at a first-stage constant current and charging and discharging the electrochromic device at a second-stage constant voltage according to the control signal. The problem that in the prior art, charging of the electrochrom